Tubular carbon nanofibers: Synthesis, characterization and applications in microwave absorption. (November 2019) - Wang, Jiqi; Huyan, Yu; Yang, Zuoting; Zhang, Aibo; Zhang, Qiuyu; Zhang, Baoliang
Abstract: In this paper, hypercrosslinked tubular polymer nanofibers (TPNF) are synthesized by Friedel-Crafts alkylation in a confined self-condensation system. Using TPNF as precursor, tubular carbon nanofibers (TCNF) with two-level pore structure are prepared by carbonization. The high specific surface area, reasonable pore structure, light weight, large aspect ratio and other significant advantages make TCNF exhibit excellent microwave absorption performance. The inner diameter of TCNF ranges from 25 to 40 nm and the wall thickness is about 30 nm. The effects of carbonization temperature on morphology, graphitization degree and pore properties are investigated. Meanwhile, the microwave absorption performance of the products at different carbonization temperature has been evaluated. The optimum carbonization temperature and absorber loading are confirmed to be 700 °C and 10%, respectively. Under this condition, the minimum reflection loss is −61.5 dB, and the effective absorption bandwidth can reach 4.25 GHz. The microwave absorbing mechanism includes moderate conductive loss, multiple reflection and scattering, interfacial polarization, Debye relaxation and good impedance matching. The obtained TCNF enriches the types and synthesis methods of carbon materials. As a highly efficient lightweight microwave absorber, TCNF possesses potential value in the synthesis and application of new composite microwave absorbing materials. Graphical abstract: Image 1